Geriatric Basics for the Neurohospitalist - Heckmann, Josef G.; Kraus, Joerg; Lang, Christoph (Neurohospitalist, 2018)
Due to the increasing age of the population, neurohospitalists are more frequently caring for old and very old people. Fundamental definitions and topics related to geriatric medicine are therefore of particular importance. In this review, common issues encountered in geriatric patients hospitalized on the neurology service are discussed. Focus is put on the geriatric assessment, multiprofessional diagnostic and therapeutic procedures, geriatric syndromes, pharmacotherapy of the aged, delirium, pain, and palliative management as they are relevant for the neurohospitalist. In addition, ethical questions are addressed.
CRIS-Team WoS Importer:2019-02-22

Neuro-Ophthalmology at the Bedside: A Clinical Guide - Heckmann, Josef G.; Vachalova, Ivana; Lang, Christoph; Pitz, Susanne (Journal of Neurosciences in Rural Practice, 2018)
Neuro-ophthalmological signs and symptoms are common in the emergency department but are a frequent source of diagnostic uncertainties. However, neuro-ophthalmological signs often allow a precise neuro-topographical localization of the clinical problem. A practical concept is presented how to perform a neuro-ophthalmological examination at the bedside and to interpret key findings under the aspect of emergency medicine with limited resources.
EVALuna2:213460

Questionable acronym Fragwürdiges Akronym - Lang, Christoph (Der Nervenarzt, 2023)
CRIS-Team Scopus Importer:2023-07-28